1167. Hospital Readmissions among Infants Diagnosed with Early-Onset Neonatal Sepsis in Connecticut. (4th December 2021) - Hudon, Rebecca; Leung, Vivian; Leung, Vivian; Petit, Susan; Banach, David
Abstract: Background: Early-onset neonatal sepsis, defined as sepsis within 72 hours of birth, results in significant infant morbidity and mortality. Readmissions associated with neonatal sepsis have not previously been well-described. Early-onset neonatal sepsis is a mandatory reportable condition in Connecticut, allowing for expanded data collection through public health surveillance to evaluate readmissions. Methods: Infants with early-onset neonatal sepsis born in Connecticut during 2007–2016 were identified from statewide surveillance data and matched with a statewide hospital discharge database. We describe readmission rates, causes and timing of readmissions, and demographic and clinical factors associated with readmission among this group. Results: Among 250 infants with early-onset neonatal sepsis matched to discharge data, 208 (82%) infants survived their initial hospitalization at birth. During the first year of life, 49 (23.6%) infants were readmitted. The most frequent reasons for readmissions were pulmonary complications (19%), systemic symptoms (17%), and gastrointestinal illness (13%). Infants with initial hospitalizations lasting longer than 30 days after birth were associated with higher rates of readmission compared to those discharged within 30 days after birth (35% vs. 19%, p=0.02). Higher readmission rates were observed among non-white infants (29% vs. 18%, p=0.06). Summary of early-onset neonatal sepsis cases and return hospital visits in Connecticut, 2007-2016 Demographic and clinical factors for Connecticut neonatal sepsis cases, 2007-2016 Reason for one-year readmissions of Connecticut neonatal sepsis cases, 2007-2016 The top three reasons for readmission include pulmonary (19%), systemic (17%), and GI problems (13%). Conclusion: Given the high proportion of infants diagnosed with early-onset neonatal sepsis who are readmitted within the first year of life, further efforts are needed to prevent readmissions among this vulnerable patient population. Non-white infants and infants with prolonged initial hospitalizations after birth might be at higher risk for readmission. These groups warrant intensified strategies to prevent readmission. Disclosures: Vivian Leung, MD, Nothing to disclose